Aortic diameter, pulse wave velocity, central aortic pulse pressure, left ventricular parameters, and diastolic dysfunction in patients with aortic aneurysm. (14th October 2021) - Gurevich, A; Emelyanov, I; Chernov, A; Zvereva, E; Zverev, D; Uspensky, V; Chernyavskiy, M; Konradi, A
Abstract: Background: The enlargement of aortic aneurysm can alters pulse wave propagation and reflection, which may influence to left ventricular (LV) afterload changes. The relevance of pulse wave velocity (PWV) and central blood pressure depending on the locus of the aneurysm for LV structure and diastolic function (DF) are not clearly unknown. Purpose: Assess the relationship between central pulse pressure (CPP), PWV and LV structure and DF in patients with ascending aortic aneurysm (AA) and abdominal aortic aneurysm (AAA). Methods: 121 patients (95 male, 63±12 years) with aortic aneurysms and preserved LV systolic function were enrolled before aortic repair. 51 patients (37 male, 54±13 years) had AA and 70 patients (58 male, 69±7 years) had AAA. CPP and PWV were measured using applanation tonometry. A echocardiographic exam was performed with a Vivid 7 GE (USA). LV mass index (LVMI) and relative wall thickness (RWT) were calculated according to standard formulas. LV filling pressure (E/Em) was estimated by Doppler-derived ratio of mitral inflow velocity (E) to septal (Em) by tissue Doppler. Transmitral flow patterns (E/A ratio of E to late (A) ventricular filling velocities) were measured with the pulsed doppler method. Results: Concentric LV hypertrophy (LVH) was observed in 51 (42%), eccentric LVH – in 35 (29%) patients. CPP was positively related with LVMI (r=0.362, P=0.001), but PWV was inversely associated with LVMI (r=−0.244, P=0.029). CPP was not associated with RWT (P≥0.5), whereas PWV was positively related (r=0.223, P=0.004). PWV decreased with increasing aortic diameter in AA and AAA (r=−0.360, P=0.029 and r=−0.315, P=0.019, respectively). 12 (23%) patients with AA and 36 (56%) patients with AAA had grade I diastolic dysfunction, 20 (40%) patients with AA and 12 (18%) patients with AAA had grade II diastolic dysfunction (P<0.001). Consequently, the E/A ratio was higher in patients with AA than in patients with AAA (1.21±0.39 vs 0.83±0.33; P=0.007). CPP and PWV was inversely associated with LV DF (E/A: r=−0.352 and −0.238; E/Em: r=−0.292 and −0.279, respectively; both P<0.05). E/A and E/Em increased with the expansion of the maximum aortic diameter at the level of the AA and AAA (E/A: r=0.612 and 0.416; E/Em: r=0.719 and 0.339, respectively; both P<0.005). RWT and LVMI were correlated with the aortic diameter at the level of the AA (r=−0.439, P=0.008 and r=0.286, P=0.05, respectively), but bore no relation with the aortic diameter at the level of the AAA. Conclusions: In patients with aortic aneurysm CPP and PWV were conjointly but differently related to LV structure. Eccentric LV hypertrophy was accompanied by a significant decrease of PWV. Reduced PWV and decreased CPP exhibited association with more severe LV diastolic dysfunction, possibly due to the apparent effect of increased aortic aneurysm diameter. LV DF was severely reduced in the patients with AA compared by patients with AAA. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Almazov National Medical Research Centre